Problem-focused coping and depression among adolescents: Mediating effect of self-esteem - Chin, Wen Cong; Wu, Shin Ling *; Tan, Soon Aun (Springer, 2019)
Adolescence is a developmental phase marked by a high risk of depressive symptoms. The Diathesis-Stress Model of Depression proposed that different types of coping strategy can determine depression level in individuals differently. It was found that low self-esteem is linked with greater depressive symptoms among adolescents. Although past studies have discovered the effects of problem-focused coping on depression, there are limited studies examining the underlying mechanism among Malaysian adolescents. Thus, the present study investigated the intervening role of self-esteem on the association between problem-focused coping and depression among adolescents. A total of 852 secondary school students in Kuala Lumpur, Malaysia were recruited through multi-stage cluster sampling. Participants filled out self-reported questionnaires on depression, self-esteem, and problem-focused coping. SPSS macro was used to analyze the mediation model. The findings showed both self-esteem and problem-focused coping negatively correlated with adolescents’ depression. Self-esteem in turn partially mediated the association between problem-focused coping and adolescents’ depression. Thus, it is recommended that intervention on reducing depressive symptoms should focus on providing adolescents with the skills to use problem-focused coping. Workshops could be conducted to heighten adolescents’ self-esteem through the help of teachers, parents and school counselors in reducing depressive symptoms among adolescents